Perceived influence of drug on academic performance of secondary school students in Ilorin metropolis, Nigeria (2015)
This study investigated the perceived influence of drug on academic performance of secondary school students in llorin West L.G.A of Kwara State, Nigeria. The descriptive design of the survey type was employed for the study. A total of (400) subject (students) in SS II and SS III ranging between the ages of 13 and 18 years old and above, male and female, formed the research sample. The variables of gender and socio-economic background were tested. A researcher structured questionnaire was used to gather data from the sample. The coefficient of reliability obtained was 0.76 using Pearson product movement statistics. Two research hypotheses were analyzed using percentages, t-test analysis of variance (ANOVA).The result from the study reveal that there is difference in the way male and female students perceived, used drug and its influence on academic performance. Also, there is difference in the way students perceived the use of drugs in relation to economic background and its influence on academic performance. Therefore, it was recommended that Senior Secondary Schools students should be educated more on the influence of drugs on academic performance; this could be done through Symposium, Seminars and also by encouraging the formation of free drugs clubs to serve as medium of campaign on illicit drug use among students arid it implication on academic performance.